Determination of glucosamine and monitoring of its mutarotation by hydrophilic interaction liquid chromatography with evaporative light scattering detector - Pazourek, Jiří (Biomedical chromatography, 2018)
Saccharides and their derivatives are typical polar analytes without a suitable UV-chromophore that are nowadays analyzed by HPLC (high-performance liquid chromatography) under HILIC (hydrophilic interaction liquid chromatography) mode. Usually an evaporative light scattering detector (ELSD) is utilized which, however, gives a nonlinear response. A procedure to overcome the problem of mutarotating (time-varying) analytes recorded with such a nonlinear response detector is described. The procedure was applied for determination of glucosamine in two commercially available pharmaceutical formulations containing the common inorganic ions that the detector gives a response to. Under optimized conditions, both the anomers of glucosamine were separated and could be determined separately. Owing to the short retention time of the analyte (a run time <4 min) and relatively slow kinetics of the anomeric conversion (equilibration time 2.5 h), mutarotation could be monitored and corresponding rate constants calculated.
Keywords: ELSD; radiační rozptyl; chromatografie kapalinová; HILIC; reprodukovatelnost výsledků; calibration; světlo; Chromatography, Liquid; isomerie; Linear Models; hydrofobní a hydrofilní interakce; Hydrophobic and Hydrophilic Interactions; Light; Isomerism; Glucosamine; glukosamin; Reproducibility of Results; lineární modely; Scattering, Radiation; mutarotation; glucosamine